Optimal and investable portfolios: An empirical analysis with scenario optimization algorithms under crisis market prospects - Al Janabi, Mazin A.M. (Economic modelling, 2014)
This paper develops scenario optimization algorithms for the assessment of investable financial portfolios under crisis market outlooks. To this end, this research study examines from portfolio managers' standpoint the performance of optimum and investable portfolios subject to applying meaningful financial and operational constraints as a result of a financial turmoil. Specifically, the paper tests a number of alternative scenarios considering both long-only and long and short-sales positions subject to minimizing the Liquidity-Adjusted Value-at-Risk (LVaR) and various financial and operational constraints such as target expected return, portfolio trading volume, close-out periods and portfolio weights. Robust optimization algorithms to set coherent asset allocations for investment management industries in emerging markets and particularly in Gulf Cooperation Council (GCC) financial markets are developed. The results show that the obtained investable portfolios lie off the efficient frontier, but that long-only portfolios appear to lie much closer to the frontier than portfolios including both long and short-sales positions. The proposed optimization algorithms can be useful in developing enterprise-wide portfolio management models in light of the aftermaths of the most-recent financial crisis. The developed methodology and risk optimization algorithms can aid in advancing portfolio management practices in emerging markets and predominantly in the wake of the latest credit crunch. •We develop optimization algorithms for investable portfolios under crisis outlooks.•Developed algorithms can aid in advancing portfolio management in financial markets.•We test optimum and investable portfolios subject to meaningful financial constraints.•Empirical results show that investable portfolios lie off the efficient frontier.•Investable portfolios cannot be achieved via Markowitz's classical portfolio approach.